Peran Kepemimpinan Kepala Desa dalam Pengembangan UMKM Desa Suwayuwo Kecamatan Sukorejo Kabupaten Pasuruan - Ilma Silfiah, Rossa; Rohmah, Maulidatur (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2024)
The role of village heads in developing MSMEs is very important because they have local authority to coordinate various programs and initiatives that support the growth of MSMEs in the region, such as providing guidance, connecting MSMEs with necessary resources, facilitating access to local and national markets, and promoting collaboration between MSMEs. By playing a proactive role, village heads can help improve the local economy and welfare of their community. This research aims to find out the leadership role of the Suwayuwo Villagei headi in the development of MSMEs. And to find out the obstacles the village head has in developing them. Thisiresearch uses aiqualitative descriptive method with data collection techniques through interviews,iobservation and documentation.iThe research results show that the village head in developing MSMEs in Suwayuwo Village has gone quite well, this is proven by holding training, and when there are events or meetings he always buys food products from MSMEs himself so that their merchandise continues to be stable and develop. Apart from that, the village head also took the initiative to utilize local potential in the village to develop MSMEs in the village. However, there are still obstacles in encouraging the development of MSMEs in Suwayuwo Village, such as budget limitations, the village funds received are very limited and must be divided for various village development needs, lack of facilities such as websites, and lack of NIB (Business Master Number) facilities for people who lack knowledge of technology.